2017
DOI: 10.1371/journal.pone.0169987
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Organization of Repetitive DNA in Woodpeckers (Aves, Piciformes): Implications for Karyotype and ZW Sex Chromosome Differentiation

Abstract: Birds are characterized by a low proportion of repetitive DNA in their genome when compared to other vertebrates. Among birds, species belonging to Piciformes order, such as woodpeckers, show a relatively higher amount of these sequences. The aim of this study was to analyze the distribution of different classes of repetitive DNA—including microsatellites, telomere sequences and 18S rDNA—in the karyotype of three Picidae species (Aves, Piciformes)—Colaptes melanochloros (2n = 84), Colaptes campestris (2n = 84)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…In addition, our data reinforced the view that the existence of one pair of microchromosomes bearing 18S rDNA clusters is apparently an ancestral character retained in Columbidae, and that repetitive sequences did preferentially accumulate in the centromeric regions of macro and microchromosomes, as well as in the W chromosomes. Additionally, despite the fact that studies with repetitive sequences in birds are still incipient, the comparison of our data with the ones for Psittaciformes, Piciformes and Galliformes ( Matsubara et al , 2015 ; de Oliveira et al , 2017 ; Furo et al , 2017 ) shows interesting variation in accumulation sites for some of them, reinforcing microsatellites as important markers for studies on karyotype evolution.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition, our data reinforced the view that the existence of one pair of microchromosomes bearing 18S rDNA clusters is apparently an ancestral character retained in Columbidae, and that repetitive sequences did preferentially accumulate in the centromeric regions of macro and microchromosomes, as well as in the W chromosomes. Additionally, despite the fact that studies with repetitive sequences in birds are still incipient, the comparison of our data with the ones for Psittaciformes, Piciformes and Galliformes ( Matsubara et al , 2015 ; de Oliveira et al , 2017 ; Furo et al , 2017 ) shows interesting variation in accumulation sites for some of them, reinforcing microsatellites as important markers for studies on karyotype evolution.…”
Section: Discussionmentioning
confidence: 51%
“…In Piciformes, a large accumulation of 10 sequences was observed on autosomes and especially on the Z sex chromosome in three woodpecker species (Picidae). The Z chromosome corresponds to the larger element of their karyotype due to the accumulation of such sequences, which increased its size ( de Oliveira et al , 2017 ). On the other hand, in Myiopsitta monachus (Psittaciformes, Psittacidae) these sequences accumulated preferentially in the W sex chromosome, which has the same size of the Z chromosome, unlike most Neognathae bird species ( Furo et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…These include flickers [10][11][12][13][14][15], sapsuckers (Sphyrapicus; [10][11][12][13][14][15], Nuttall's/Ladder-back woodpeckers [16] and Redbellied/Golden-fronted woodpeckers [10][11][12][13][14][15]. More recently, woodpeckers have gained attention for the high amount of repetitive DNA found in their genomes relative to other bird taxa [17][18][19], the result of high levels of genome-wide transposable elements (TEs), which are scarce in most bird genomes [20]. Manthey et al [21] surveyed several woodpecker genomes, and found that TEs make up 17-31% of woodpecker genomes, compared to <10% for other bird species.…”
Section: Introductionmentioning
confidence: 99%
“…However, we note that one-to-one synteny to the Gallus assembly was lacking for the larger chromosomes, indicative of chromosomal splitting since the Gallus-Colaptes common ancestor has occurred. Members of Picidae are known for containing a high number of chromosomes, particularly micro-chromosomes (Kaul and Ansari 1978), and karyotypes of Colaptes have been shown to consistently have a larger number of chromosomes when compared to Gallus (Pollock and Fechheimer 1976;de Oliveira et al 2017).…”
Section: Sequencing Genome Assembly and Synteny Mappingmentioning
confidence: 99%